Moderating effects on residents’ willingness in waste sorting to improve waste handling in Dammam City, Saudi Arabia - Labib, Ossama; Manaf, Latifah; Sharaai, Amir Hamzah; Mohamad Zaid, Siti Sarah (MDPI, 2021)
While the total amount of municipal solid waste (MSW) in Dammam city was about 13 million tons in 2013, it is expected to reach about 18.4 million tons in 2025. Although the main problem in Dammam city is an increase in solid waste production without any formal treatment except landfilling, the lack of waste segregation greatly affects the residents’ handling practices of solid waste due to incorrect disposing practices. The objective of this study explored the possibility of Dammam residents’ participation in sorting and recycling to improve MSW handling and to measure the influence of psychological factors which affecting residents’ willingness to participate in waste handling regarding socioeconomic levels and moderating effects. This study also examined various respondents’ perspectives on sorting and recycling sustainable waste and the handling of waste generation. This study covered most Dammam communities, with a gender distribution of 56% males and 44% females and the monthly income ranging from SR700 to SR12,000. The descriptive analysis showed that of the 450 participants, 170 (37.8%) were in the middle-income levels, 199 (44.2%) were in the high-income levels and 81 (18%) were in the low-income levels. The moderating effect of income was observed between attitude and willingness to sort and recycle waste in the low-income levels and high-income levels groups. Additionally, an association was found between market incentives and willingness to sort and recycle waste in the low-income levels and high-income levels groups. The gender status of the participants had a moderating effect on the relationship between market incentives and willingness to sort and recycle waste in males and females. Additionally, the moderating effect of social influence on households’ willingness to sort and recycle waste was moderated by gender in males and females.